Designing A Web-Based Mikrotik Hotspot Server Monitoring Application - Farhan Hazairin; Toibah Umi Kalsum; Yessi Mardiana (Penerbit Jurnal Indonesia, 2024)
This research was conducted to build a hotspot network server monitoring system and implement a hotspot network server management system and hotspot network users. In this study using the Experiment research method. In this study, a web-based proxy hotspot server monitoring application was designed. The results of the experiment are then documented to analyze so that the right recommendations are produced for designing a web-based proxy hotspot server monitoring application. From the results of this analysis, conclusions will be drawn about the benefits, functions and advantages of the system that has been built. The results of this study indicate that the web-based proxy hotspot server monitoring application can be applied to hotspot servers on proxy routers, where the test results show that the application can monitor users with the results there is 1 user who is active using user1 login and getting IP address 10.5.50.253 with an uptime of 1 minute 49 seconds. This application will display all users who are using the hotspot network, where the number of users displayed will adjust how many users are currently connected. The hotspot server monitoring application can also monitor the amount of download (RX) traffic of 14.04 MB and upload (TX) of 2.43 MB on the ether1 interface and the amount of download (RX) traffic of 2.44 MB and upload (TX) of 14.47 MB on the ether2 interface. The amount of this traffic depends on the use of the hotspot network by users in the hotspot network. In addition, this application can also monitor hotspot server logs by displaying activities that are happening on the proxy router such as login request activities, IP address requests, login attempts by users and others. This application can also be used for hotspot user management where test results show the application can add and also delete users who can connect to the hotspot network.